Boost Irradiation Integrated to Whole Brain Radiotherapy in the Management of Brain Metastases - Dobi Ágnes (PATHOLOGY AND ONCOLOGY RESEARCH, 2020)
Our retrospective analysis aimed to evaluate the clinical value of dose intensification schemes: WBRT and consecutive, delayed, or simultaneous integrated boost (SIB) in brain metastasis (BM) management. Clinical data and overall survival (OS) of 468 patients with BM from various primaries treated with 10 x 3 Gy WBRT (n = 195), WBRT+ 10 x 2 Gy boost (n = 125), or simultaneously 15 x 2.2 Gy WBRT+0.7 Gy boost (n = 148) during a 6-year period were statistically analysed. Significant difference in OS could be detected with additional boost to WBRT (3.3 versus 6.5 months) and this difference was confirmed for BMs of lung cancer and melanoma and both for oligo- and multiplex lesions. The OS was prolonged for the RPA 2 and RPA3 categories, if patients received escalated dose, 4.0 vs. 7.7 months; (p = 0.002) in class RPA2 and 2.6 vs. 4.2 months; (p < 0.0001) in the class RPA 3 respectively. The significant difference in OS was also achieved with SIB. The shortened overall treatment time of SIB with lower WBRT fraction dose exhibited survival benefit over WBRT alone, and could be applied for patients developing BM even with unfavourable prognostic factors. These results warrant for further study of this approach with dose escalation using the lately available solutions for hippocampus sparing and fractionated stereotactic irradiation. The simultaneous delivery of WBRT with reduced fraction dose and boost proved to be advantageous prolonging the OS with shortened treatment time and reduced probability for cognitive decline development even for patients with poor performance status and progressing extracranial disease.